Epidemiological Study of Stroke Cases Presenting to the Emergency Department of a Tertiary Hospital: An Observational Study - Bibek Rajbhandari; Yogendra Man Shakya; Ramesh Kumar Maharjan; Yagya Laxmi Shakya; Shiva Sharma Aryal; Pratiksha Bhandari; Olita Shilpakar; Ram Prasad Neupane; Rajan Narayan Nakarmi; Cimona Shrestha (Journal of Nepal Medical Association)
Introduction: Stroke remains a major global health burden, ranking as the second leading cause of death and third leading cause of disability worldwide. Low- and middle-income countries, including Nepal, face a disproportionate share of this burden, characterized by delayed treatment and limited healthcare infrastructure. This study aimed to determine the epidemiological profile of stroke cases presenting to the emergency department of a tertiary hospital in Nepal.